Proposed Repair to Minimize the Difference of Delivery Items Using Fishbone and 5W + 1H - Somadi Somadi; Akhdan Ijlal Muzakki (Jurnal Logistik Indonesia, 2021)
Bekasi post office 17000 is an UPT PT Pos Indonesia located in the Regional 4 working area of West Java. Based on data obtained from irregularity website PT Pos Indonesia in September-November 2019, various problems occurred in indoor process of Bekasi Post Office. The biggest problem is that the difference between the barangs shipped with 56 occurrences. The search process must be carried out to find these missing barangs, so that further investigation is needed which causes the delivery duration exceed the standard delivery time (SWP). This study aims to determine the factors that cause the difference between the manifest and the physical delivery of the consignment and provide suggestions for improvement. The research method used fishbone analysis techniques and 5W + 1H. Based on the results of the research, the difference in consignment barangs is less due to the barang being not scanned, x-ray failure, wrong bagging, and error scanning device. Proposals for improvements to minimize the difference in barangs being shipped are conducting briefings and socializing work SOPs to officers, imposing rewards and punishments for enforcing SOPs, checking empty bags, and coordinating with the facilities section so damaged scanner can be repaired.